A virtude política na Terra de Santa Cruz: ambição e insolência na Gênese da República Nova - Gonçalves, Leandro Ramos (2015)
In the widespread rhetoric of consolidation masks a paradox inside of the brazilian political scenario: the republican system was build in the prewritten institutions on the Constituitional Letter of 1988 as a institucional arrangement and after twenty five years of exercise didn t crumble in front of adversity, like had always happened in Brazil s politics; however, researchs about people s political imaginary doesn t show a remarkable evolution of the republican way of life that happened among this institution. In view of this problematic, this work it s intented to try to understand the experience of the past and presente things, trying to verify if the contemporaneous brazilian State built this regime facing freedom like it was supposed to do. The methodology used was inspired by Niccolo Machiavelli s categories for analysis: facing the Nova Republica s as State, that has form and matter, build and orderly from the Virtue of the great, while princes, for the establishiment of the people, starting with the moment provided by Fortune during the period